Dynamics of One-Consumer-Two-Resources Ecological System with Beddington-Deangelis Functional Response - Sarwardi, Sahabuddin; Mandal, Md. Reduanur; Gazi, Nurul Huda (Journal of Applied Nonlinear Dynamics, 2026)
In this paper we study a one-consumer-two-resources ecological system with simple mass action and Beddington-DeAngelis functional responses. The essential mathematical features of the present model have been analyzed thoroughly in terms of the local and the global stability and the bifurcations arising in some selected situations as well. The ranges of the significant parameters under which the system admits a Hopf bifurcation are investigated. The explicit formulae for determining the stability, direction and other properties of bifurcating periodic solutions are also derived with the use of both the normal form and the central manifold theory (cf. Carr [1], Hassard et al. [2]). Numerical illustrations are performed finally in order to validate the applicability of the model under consideration.